Origin and development of Unani medicine: an analytical study - Islam, Arshad (2016)
The history of medicine is a fascinating account of the human battle against illness. As civilization advances and disease patterns change, medical science also develops. Unani is the ancient Greek system of medicine that evolved throughout the ancient world and which was fostered in the Islamic realms, based on ancient logic and timeless rules encapsulating a cosmological view of human health and the universe. Generations of Muslim scholars acquired and developed Greek treatises and commentaries on medicine and science in general, critically examining, collating, revising and enriching the knowledge of ancient Greek, Persian, Egyptian and Indian science during what is known as the Golden Age of Islam. This study traces the history of the origin and development of Unani medicine in the Islamic world and its later flowering in the Indian Subcontinent. Based mainly on Arabic, Persian, Urdu and English sources, the study focuses on the intellectual legacy of the Muslims in the development of Unani medicine and their interest in the progress of medical sciences, when a number of classical works were produced by great Muslim scholars during this period that provide evidence of organized medical care that provided the basis for modern medicine as it emerged from the 17th century onwards in Europe. The early Muslim scholars’ works were focused on the integration or Islamicisation of human knowledge in the areas of medical and health-care sciences as well as those who seek to understand the role of moral values and Maqasid al-Shari’ah (objectives of Shariáh) in medical and healthcare practices in a more comprehensive framework. Keywords: Ayurvedic medicine, Egyptian medicine, Greek medicine, Persian medicine, Unani medicine